Malaysian social enterprise blueprint 2015-2018: what's next? Mohd Ali Bahari Abdul Kadir ... [et al.] - Abdul Kadir, Mohd Ali Bahari; Zainudin, Ainul Hafiza; Harun, Umi Syukriah; Mohamad, Nur Aisyah; Che Harun, Nur Haslyna Atyra (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
Social enterprise plays a noteworthy role in the society as it endlessly delivers social value very much needed by the community. In 2015, Malaysia has launched its Malaysian Social Enterprise Blueprint, a three-year blueprint that entails pivotal strategy to promote and accelerate development of the sector, of which by the year 2018, supposedly be self-sustaining, equitable, and people-centric in order to empower impact-driven entrepreneurs. The blueprint highlighted several challenges and issues that need to be resolved in order to fully unleash the potential of social entrepreneurship in Malaysia. This paper emphasizes the conundrums in legal and policy structures of social enterprise, which do not run parallel with the practices of other countries and need attention from all the stakeholders. In the course of writing this paper, references are made to South Korea and United Kingdom (UK); countries which legally recognize and shelter the well-being of social enterprises via legal enactment and entity registration. A legal framework is needed to provide legal recognition to social enterprises and to help plaster the loopholes in the area pertaining to financial distribution and support.